Réponses

  • Utilisateur Brainly
2014-09-21T08:26:46+02:00
a.
- x - 6,5 = 4x + 1
- 1 - 6,5 = 4 x 1 + 1
- 7,5 ≠ 5
⇒ Faux

b.
- x - 6,5 = 4x + 1
2 - 6,5 = 4 x 2 + 1
- 4,5 ≠ 9
⇒ Faux

c.
1,5 - 6,5 = - 4 x 1,5 + 1
- 5 = - 6 + 1
- 5 = - 5
⇒ Vrai
2014-09-21T08:51:35+02:00
- x - 6.5 = 4x + 1
Pour :
a) x = 1
- x - 6,5 = 4x + 1
- 1 - 6,5 = 4 *  1 + 1
- 1 - 6,5 = 4 + 1
- 7,5 ≠ 5
L'égalité est fausse


b) Pour x = - 2
- x  - 6,5 = 4x + 1
- (- 2) - 6,5 = 4 * - 2 + 1
2 - 6,5 = - 8 + 1
-  4,5 ≠ - 7
L'égalité est fausse


c) Pour  x = - 1.5
- x - 6,5 = 4x + 1
- (- 1,5) - 6,5 = 4 * - 1,5 + 1
1,5 - 6,5 = - 6 + 1
-  5 = - 5
L'égalité est vraie